Medicinal Plants used for traditional healing practices among the tribal communities of Ri-Bhoi District, Meghalaya, India - Paul, Sumana; Das, Mautushi (Current Botany, 2025)
This study aimed to document and analyze the medicinal plants used by tribal communities in the Ri-Bhoi district of Meghalaya, India, and to evaluate their significance in traditional healing practices. Through the collection of ethnomedicinal knowledge using standard questionnaires and group interviews, the research identified 50 medicinal plant species across 35 families employed in treating 38 common ailments. The study assessed the use value (UV), informant consensus factor (ICF), and fidelity level (FL) of these plants to gauge their importance and effectiveness. The analysis revealed that Euphorbia neriifolia L. holds the highest use value (UV=0.36), indicating its frequent and significant use among local traditional healers. This plant, along with others identified, demonstrates a broad application in addressing various health conditions prevalent in the region. The study also noted a substantial degree of consensus among informants regarding the therapeutic uses of these plants, with ICF values ranging from 0.33 to 0.74. This suggests a strong agreement on the medicinal applications of specific plants for distinct disease categories. The fidelity levels (FL) of the medicinal plants varied between 33.33% and 100%, reflecting both the reliability and the degree of acceptance of these plants in traditional medicine. The high fidelity values for certain plants underscore their critical role in local health practices. Overall, this study underscores the rich ethno medicinal knowledge embedded within the Ri-Bhoi district’s tribal communities and highlights the need for ongoing documentation and preservation of this traditional wisdom. The findings contribute valuable insights into the use and significance of local flora in traditional healing, which could inform future research and conservation efforts.